IPTEKS PERENCANAAN DAN REALISASI ANGGARAN PROGRAM KERJA PADA KELURAHAN SINGKIL II MANADO - Wawointana, William Juan; Manimbaga, Federicky; Wangkar, Anneke (Universitas Sam Ratulangi, 2018)
This study aims to determine the planning process and realization of the activity budget at the Singkil 2 Manado sub-district office. data collected using the interview method. This type of research uses qualitative methods. planning and realization of the budget activities are prepared through MUSRENBANG and according to the community agreement also fits the 4 stages of preparation. Based on these results, the Singkil 2 sub-district requires the socialization of the results of future plans to the community regarding the central government's decision to realize the activity budget.Keywords :MUSRENBANG,budget planning, budget realization